Cross-Cultural Comparisons of Review Aspect Importance - Nakayama, Makoto; Kanayama, Hiroshi; Nasukawa, Tetsuya (International Journal of Informatics and Information Systems, 2018)
Previous text mining studies identified key common aspects in online restaurant reviews. However, it is not clear how important these aspects are for consumers. In this exploratory study, we used Yelp restaurant reviews on an ethnic food item, ramen noodles, and assessed the importance of each aspect to both U.S. and Japanese consumers. The results show that food and atmosphere are far more important than the other common aspects in both the U.S. and Japan. However, we found noticeable differences between consumers in the two countries regarding how the food aspect plays a role on star ratings. Both implications and a future research agenda are discussed.